2011
DOI: 10.1039/c0cp02151b
|View full text |Cite
|
Sign up to set email alerts
|

EPR parameters of amino acid radicals in P. eryngii versatile peroxidase and its W164Y variant computed at the QM/MM level

Abstract: Quantum mechanics/molecular mechanics (QM/MM) methods, employing density functional theory (DFT), have been used to compute the electron paramagnetic resonance (EPR) parameters of tryptophan and tyrosyl radical intermediates involved in the catalytic cycle of Pleurotus eryngii versatile peroxidase (VP) and its W164Y variant, respectively. These radicals have been previously experimentally detected and characterized both in the two-electron and one-electron activated forms of the enzymes. In this work, the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 114 publications
6
35
0
Order By: Relevance
“…The role of such hydrogen bonds in lowering the g x value is in agreement with previous works on tyrosine radicals: in particular, this effect has been evidenced also in the catalytic cycle of the P. eryngii VP variant following the Tyr164 protein radical formation 46,60 . On the other hand, Tyr147 in AauDyP is involved in a weaker hydrogen bond with solvent water molecules (1.890Å) (Fig.…”
Section: W-band Epr Spectra and Qm Calculations Of Aaudyp And Its Dirsupporting
confidence: 79%
“…The role of such hydrogen bonds in lowering the g x value is in agreement with previous works on tyrosine radicals: in particular, this effect has been evidenced also in the catalytic cycle of the P. eryngii VP variant following the Tyr164 protein radical formation 46,60 . On the other hand, Tyr147 in AauDyP is involved in a weaker hydrogen bond with solvent water molecules (1.890Å) (Fig.…”
Section: W-band Epr Spectra and Qm Calculations Of Aaudyp And Its Dirsupporting
confidence: 79%
“…A similar g-tensor anisotropy effect would be expected for a hydroxylated Trp radical because the radical spin density is typically delocalized over the entire indole ring (22)(23)(24)(25)(26)(27). Therefore, βTrp57-OH of preMADH would be expected to have a Δg value greater than that of Trp radicals and closer to that of Tyr radicals.…”
Section: Resultsmentioning
confidence: 89%
“…The rationale for this proposal is the higher redox potential of the tryptophanyl cation radical (ϳ1.15 V) as compared with its neutral form (ϳ1.01 V) (55) that would facilitate lignin oxidation. Proton abstraction during phenol oxidation is generally simultaneous to electron abstraction, and this has been shown for tyrosyl radical formation in the W164Y VP variant (53). However, spectroscopic studies suggested that under acidic conditions, a cation-like radical (or H-bonded neutral radical) is formed at the high redox potential short-lived Tyr-161 of photosystem II (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…In the EPR spectrum of the tyrosyl radical from peroxideactivated T. cervina LiP*, the g x value with the acceptable variation (g x ϭ 2.0078 -2.0082) suggests the existence of a hydrogen bond with a length of 1.8 -2.0 Å (51) because there is a clear relationship between the g x value and the hydrogen bond strength (52). The recent quantum mechanics and molecular mechanics calculations on the VP W164Y variant have demonstrated that the proton transfer to the nearby Glu-243, during tyrosine oxidation, proceeds barrierless, directly yielding the Tyr-164 neutral radical, but the variant is inactive because reorganization of hydrogen interactions (by water molecules and neighbor residues) precludes an easy recovery of the proton by the tyrosine residue (53). In the crystal structure of T. cervina LiP*, the phenolic hydroxyl group of Tyr-181 forms hydrogen bonds with the backbone carbonyl of Val-336 (2.72 Å) and with Wat-26 (2.74 Å) that forms two other H-bonds to His-39 (2.65 Å) and heme internal propionate (2.82 Å).…”
Section: Discussionmentioning
confidence: 99%